Relating shading levels and distance from natural vegetation with hemipteran pests and predators occurrence on coffee - Karungi, J.; Nambi, N.; Ijala, A. R.; Jonsson, M.; Kyamanywa, S.; Ekbom, B. (Journal of applied entomology, 2015)
The study was carried out to determine the effect of shading levels and/ or distance from the natural alpine vegetation (NAV) on the occurrence of two insect functional groups: hemipteran herbivores and generalist predators in farmers’ coffee fields in the Mt. Elgon region of Uganda. Three distance categories from the NAV, that is (i) 0–250 m; (ii) 250– 1000 m and (iii) 1000–1500 m, were used to demarcate farms in the first stage of selection, and within each distance category, three levels of shading, that is (i) no shade, (ii) moderate shade and (iii) full shade, were used for final selection of coffee farms for the study. A total of 90 individually owned coffee fields were studied; 30 for each distance category, of which 10 represented each shading level. In two separate rounds, inventories of scale insects (Coccus spp.), antestia bugs (Antestiopsis spp.), root mealybugs (Planococcus spp.) and aphids (Toxoptera aurantii) on coffee plants were made for the hemipteran herbivores, whereas ants (Formicidae) and spiders (Araneae) were recorded for the predatory taxa. The results showed that the interaction between distance from the NAV and shading level consistently influenced the occurrence of the insects in both functional groups. For scale insects, root mealybugs and ants, it was closest to the NAV that shading-level effects were most discernible and generally limiting. To the contrary, the occurrence of aphids and spiders increased with the increase in the level of shading for plants furthest from the NAV. These results indicate that if inclusion of shade trees is to be a strategy in ecological pest management, the level of shading should be determined basing on the insect taxa as well as other pertinent factors in the landscape.
Keywords: Ants; Aphids; Arabica coffee; Mealybugs; Scale insects; Spiders